Natural compounds from seeds of Cassia grandis L.f - Luan, Ngo Quoc; Tao, Nguyen Cong; Hai Tien, Vu Thi; Nghia, Nguyen Ba; Dung, Le Tien; Tri, Mai Dinh; Han, Nguyen Ngoc; Phi Phung, Nguyen Kim (Vietnam Journal of Chemistry, 2016)
For the first time, four known natural compounds from extracts of seeds of Cassia grandis L.f including o-anisic acid (1), chrysophanol (2), pulmatin (3) and (-)-epiafzelechin (4) have been isolated. Their structures were elucidated by MS, NMR spectra and comparison with published data. Three in isolated compounds were tested for anticancer, antioxidant and antimicrobial activities, only pulmatin could inhibit to E. coli, B. subtillis and S. aureus. Keywords. Cassia grandis L.f, o-anisic acid, chrysophanol, pulmatin, (-)-epiafzelechin.